An in-depth analysis of digital marketing trends and prospects in small and medium-sized enterprises: utilizing bibliometric mapping - Laila, Nisful; Sucia Sukmaningrum, Puji; Saini Wan Ngah, Wan Azman; Nur Rosyidi, Luthfi; Rahmawati, Indah (Cogent OA, 2024)
This study presents a bibliometric analysis of digital marketing research within small and medium-sized enterprises (SMEs) spanning from 1985 to 2024. By analyzing 699 publications from the Scopus database, it aims to provide a comprehensive overview of the field’s evolution and current research focuses. The analysis leverages VOSviewer and RStudio’s ‘Biblioshiny’ tools for their robustness in data handling and bias reduction, facilitating a detailed exploration of collaborative networks, key themes and impactful literature. Thematic analysis, enhanced by case studies, identifies emerging areas such as commerce, marketing, digital transformation, costs and Covid-19, offering insights into future research directions. Despite its reliance on Scopus-indexed articles as a limitation, the research contributes to the academic and practical understanding of digital marketing in SMEs, highlighting critical areas for future exploration and development. © 2024 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.